Single-pot reductive rearrangement of furfural to cyclopentanone over silica-supported Pd catalysts - Date, Nandan S.; Kondawar, Sharda E.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (ACS Omega, 2018)
Direct one-pot hydrogenation of furfural (FFR) to cyclopentanone (CPO) was investigated over different silica-supported Pd catalysts. Among these, 4% Pd on fumed silica (4%Pd/f-SiO2) showed remarkable results, achieving almost 98% furfural (FFR) conversion with similar to 89% selectivity and 87% yield to cyclopentanone at 165 degrees C and 500 psig H-2 pressure. More interestingly, the fumed-silica-supported catalyst tuned the selectivity toward the rearrangement product, i.e, cyclopentanone, whereas all of the other supports were found to give ring hydrogenation as well as side chain hydrogenation products due to their parent Bronsted acidity and specific support properties. X-ray diffraction data revealed the presence of different phases of the face-centered cubic lattice of metallic Pd along with lowest crystallite size of 15.6 nm in the case of the silica-supported Pd catalyst. However, Pd particle size was found to be in the range of 5-13 nm with even dispersion over the silica support, confirmed by high-resolution transmission electron microscopy analysis. While studying the effect of reaction parameters, it was observed that lower temperature gave low furfural conversion of 58% with only 51% CPO selectivity.. Similarly, higher H-2 pressure lowered CPO selectivity with subsequent increase in 2-methyl furan and ring hydrogenation product 2-methyl furan and 2-methyl tetrahydrofuran. Thus, as per the requirement, the product selectivity can be tuned by varying the type of support and/or the reaction parameters suitably. With the help of several control experiments and the characterization data, a plausible reaction pathway was proposed for the selective formation of cyclopentanone.